Drop-Weight Impact Test for Measuring the Damage Resistance of Aero Helmets - Abdullah, M. N.; Yaakob, M. S.; Muda, M. K. H.; Mustapha, F. (Journal of Advanced Research in Applied Mechanics, 2020)
This paper represents the performance of aero helmets in a drop-weight impact testing. The potential energy to be used was defined as mass and drop height is to be 4.94 ft-lb (6.7J) multiplied by the specimen thickness. Helmet standards require helmets to be designed only to survive a simple drop test onto an anvil. Two helmets being tested was attached to the test rig in the particular desired impact orientation. The main advantages of this process are the object is attached to the test rig during impact will provides more realistic drop-weight impact and accurate data. Data characterizing from the impact test was collected and analyzed to evaluate the material properties of kenaf and flax. By comparing the peak deformation and absorbed energy, the kenaf aero helmet show a better performance in absorbing energy with less deformation than flax aero helmet.